PENGEMBANGAN USAHA LAMPU HIAS RUMAH UKIR BAMBU DI KABUPATEN BANGKALAN - Hasan, Buaddin; Chairuddin, Chairuddin (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. Although the decorative lighting business is relatively new, handicrafts with the main bamboo material and various motifs are very popular with the community because of its unique and natural shape. In general, these decorative lights are made of materials such as glass, crystals from plastic, or stainless steel. In order to overcome the problems faced by partners, the implementation team collaborated with partners to provide various training and assistance in business development by utilizing science and technology. This community service program is carried out by the community education method, which is to provide training and mentoring to develop various designs of carving motifs using computer assistance, besides training in immersion techniques and paint finishing and drying techniques using an oven system. While the second method is the substitution of science and technology, which provides an overview of how to market products to partners in order to be able to utilize social media as a marketing tool, social media used between Blogger, IG, Facebook and WA. The results obtained in the implementation of this community partnership program were an increase in the income of bamboo carving businesses reaching 50% of the before. This happens because of the marketing system that has used social media, an increase in the production of decorative lights as much as 60% of the original production. The development of variations in carving motifs that are adjusted to the order and certain momentsAbstrak. Meski usaha lampu hias tergolong baru, kerajinan tangan dengan bahan utama bambu dan berbagai motif tersebut sangat diminati oleh masyarakat karena bentuknya yang cukup unik dan alami. Pada umumnya lampu hias ini terbuat dari bahan-bahan seperti kaca, kristal dari plastik, ataupun stainless steel. Dalam rangka mengatasi permasalahan yang dihadapi mitra, tim pelaksana bekerjasama dengan mitra memberikan berbagai pelatihan dan pendampingan dalam pengembangan usaha dengan memanfaatkan IPTEK. Program pengabdian ini dilakukan metode pendidikan masyarakat yaitu memberikan pelatihan dan pendampingan mengebangkan berbagai desain motif ukir menggunakan bantuan komputer, selain itu pelatihan teknik perendaman dan teknik finishing cat dan pengeringan menggunakan sistem oven. Sedangkan metode yang kedua adalah substitusi IPTEK yaitu memberikan gambaran cara memasarkan produk kepada mitra agar mampu memanfaatkan media sosial sebagai sarana pemasaran, media sosial yang digunakan antara Blogger, IG, Facebook dan WA. Hasil yang diperoleh dalam pelaksanaan program kemitraan masyarakat ini adalah adanya peningkatan pendapatan usaha rumah ukir bambu mencapai 50% dari semula. Hal ini terjadi karena sistem pemasaran yang sudah menggunakan media sosial, adanya peningkatan hasil produksi lampu hias sebeasar 60% dari produksi semula. Adanya pengembangan variasi motif ukir yang disesuaikan dnegan pesanan dan moment tertentu.